Penggunaan Keping Compact Disc (CD) sebagai Kisi Difraksi untuk Menentukan Indeks Bias Zat Cair - Ellyana, Rossy Lydia; Santoso, Sugeng (Jurnal Teori dan Aplikasi Fisika, 2024)
Research on the use of compact disc (CD) chips as a diffraction grating to determine the refractive index of liquids aims to determine the value of the refractive index of liquids through the diffraction lattice constants of compact disc (CD) chips, both filled with data and not filled with data. The sample used in this study was pure water (aquadest). The research method begins with making lattice holders, supports, liquid containers and cleaning the CD layer. The lattice constant of the CD is determined by irradiating the CD with an air medium using a laser light source and a dark-bright (diffraction) pattern appears on the screen. Measurement of the distance from the central slag to the light was first measured using a paper scale that had been attached to the screen, then analyzed using a weightless linear regression equation on Microsoft Excel. Measurements were made by varying the lattice distance to the observation screen. The same method is carried out in pure water medium (aquadest). Based on the results of these measurements, the refractive index value of pure water (aquadest) for the red laser pointer on an empty data CD is (1.29 ± 0.04) and on a full data CD is (1.40 ± 0.05). Meanwhile, the refractive index value of pure water (aquadest) for the green laser pointer on an empty data CD is (1.31 ± 0.08) and on a full data CD is (1.38 ± 0.08). Keywords: Diffraction Grating, Compact Disc (CD), Linear Regression, Aquadest Refractive Index.